2000
DOI: 10.1002/1096-9861(20000821)424:2<283::aid-cne7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Steroid regulation of octopamine expression during metamorphic development of the mothManduca sexta

Abstract: Octopamine (OA), a biogenic amine similar to norepinephrine, has profound and well-documented actions on the nervous systems of invertebrates. In the insect, Manduca sexta, we examined the developmental plasticity of OA synthesis, studied its endocrine regulation, and observed previously undescribed OA-immunoreactive (ir) neurons. We found that levels of tyramine beta-hydroxylase (TbetaH), an essential enzyme for the biosynthesis of OA, increase during metamorphosis. Based on the established and influential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Incubation of crude nerve cord extract with tyramine results in the formation of OA, which is detectable by ELISA assay. This assay requires catalase (Wallace 1976, Lehman et al 2000a and is based on the conversion of tyramine to OA by the TBH contained in the tissue protein extract. Previous studies conducted on several animals including cockroach used radioactive HPLC detection technique (Lehman et al 2000a,b), which is a very precise assay for activity quantification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incubation of crude nerve cord extract with tyramine results in the formation of OA, which is detectable by ELISA assay. This assay requires catalase (Wallace 1976, Lehman et al 2000a and is based on the conversion of tyramine to OA by the TBH contained in the tissue protein extract. Previous studies conducted on several animals including cockroach used radioactive HPLC detection technique (Lehman et al 2000a,b), which is a very precise assay for activity quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical property analysis of a partially purified TBH from the thoracic nervous system of the lobster Homarus americanus had demonstrated that TBH is necessary for the hydroxylation of tyramine to produce OA and that this reaction is dependent on pH, ascorbic acid, copper, and catalase (Wallace 1976, Lehman et al 2000a. During Manduca sexta development, TBH activity is increased in the brain and in the ganglia, in correlation with an increase in OA levels during metamorphosis reflecting that OA levels are developmentally regulated (Lehman et al 2000a,b).…”
Section: Introductionmentioning
confidence: 99%
“…3 H]tyramine to [ 3 H]OA and has been used previously to characterize T␤h in the developing nervous system of the hawk moth, Manduca sexta (Lehman et al, 2000a;Lehman et al, 2000b). Here, individually dissected bee brains were each homogenized in 10·l bee saline and 2·l samples were assayed for total protein concentration.…”
Section: T␤h Activity Assaysmentioning
confidence: 99%
“…This could suggest an inhibition of RFamide expression occurring during normal development between P8 and P12, which is absent after early 20E injection. On the other hand the lack of a plateau phase could simply reflect the fact that a single hormone injection does not mimic the pupal ecdysteroid peak as well as a continuous hormone infusion might do (Lehman et al, 2000). Furthermore, synaptotagmin staining revealed that not only the presence of RF-amides, but also the formation of glomeruli, occurred earlier than during normal development.…”
Section: Developmental Regulation Of Rfamide Immunoreactivitymentioning
confidence: 99%
“…The pupal 20E peak regulates the fusion of thoracic and abdominal ganglia (Amos et al, 1996), it controls cell proliferation during genesis of the optic lobes and the retina but also programmed cell death of optic lobe neuroblasts Truman, 1998a,b, 2000). Specifically, 20E also regulates the pupal expression of tyramine β-hydroxylase, an essential enzyme for octopamine biosynthesis (Lehman et al, 2000). We recently showed that 20E injections early in metamorphosis lead to elevated concentrations of the second messenger molecule cyclic guanosine monophosophate in LC neurons, which during normal development does not occur before stages P7/8 (Schachtner et al, 1998(Schachtner et al, , 1999.…”
Section: Developmental Regulation Of Rfamide Immunoreactivitymentioning
confidence: 99%